Cheilostome Bryozoa of the northern Persian Gulf, Iran - Baradari, H.; Nasrolahi, A.; Taylor, P.d. (Zootaxa, 2019)
This paper describes 15 cheilostome bryozoan species obtained from 15 sampling sites along the northern coast of the Persian Gulf in Iran. Two of the cheilostomes are described as new species: Parasmittina cryptoavicularia n. sp. and Trematooecia persica n. sp. The majority of species found in this study (67%) have a tropical to subtropical Indo-Pacific distribution, while the remainder are more widely distributed. Several are fouling species known from warmer seas around the globe. Further sampling efforts are needed to obtain a better estimate of the true bryozoan diversity in the region which is almost certainly much greater than the 15 species described in this study.